Examples of high performance liquid chromatography (HPLC) application in marine ecology studies in the northern Adriatic - Vesna Flander-Putrle (Natura Sloveniae)
Photosynthetic pigments have proved to be useful biomarkers of the abundance, composition and physiological status of the phytoplankton biomass in the marine environment. Using HPLC pigment analysis, we determined phytoplankton community structure in three different marine environments: in the area of a fish farm, in the area of sewage outlets, and in the mucilaginous aggregates. At the reference site we observed seasonal changes with prevalence of fucoxanthin-containing phytoplankton (i.e. diatoms) during winter/spring and autumn. In the fish farm area the concentration of chlorophyll a degradation products was higher, whereas in the locally enriched environment of sewage outlets we observed only small changes in taxonomic composition and phytoplankton biomass. The impact of season is more expressed than the impact of sewage discharge. With the use of HPLC pigment analysis we determined the development of phytoplankton community in different stages of mucilage aggregates. Phytoplankton biomass was composed primarily of diatoms, and as the aggregates aged, diatoms increased in the relative biomass. Our examples have proven the usefulness and suitability of HPLC pigment analysis in marine ecology studies.